Extraction of Phoenix Dactilyfera seeds oil using supercritical carbon dioxide / Noor Aiysah Aris - Aris, Noor Aiysah (2014)
Date fruits {Phoenix Dactylifera L.) contain high nutrients such as carbohydrate, fat, protein, dietary fibre, vitamins, minerals and antioxidant. However, the waste (seeds) from date fruit was always neglected since it cannot be consumed as it is, although it contains lots of nutrient same as the fruit. Most of the previous researcher extracted date seeds oil using conventional method. However, the conventional method for extraction of date seeds oil by using organic solvent is toxic and harmful towards human and environment. Thus, supercritical carbon dioxide (SC-CO₂) extraction method is introduced as a clean technology to extract oil from date seed. It can also be an alternative method to replace the current conventional method which utilized organic solvent. The objectives of this study are to extract oil from date seed type Mariami from Middle East, within a range of temperature (40, 50, 60, 70 and 80˚C) and pressure (27.6, 34.5, 41.4, 48.3 and 55.2MPa). In addition, to determine the best condition for highest oil yield, to identify the valuable components in the oil using gas chromatography equipped with mass spectrometry (GC-MS) and also to model the solubility data of date seed oil in SC-CO₂. The highest oil yield achieved was 3.3% with the solubility of 0.174 g oil/kg CO₂ achieved at pressure 55.2MPa and temperature of 50 ˚C. Analysis of component in the oil using GC-MS showed that the components detected were lauric acid, myristic acid, palmitic acid, linolelaidic acid, laurostearic acid, oleic acid, stearic acid and ascorbyl palmitate. Solubility data from experiment fitted well with the correlation model. Based on Paired T-test analysis, Chrastil model, Del Valle-Aguilera model and Adachi-Lu were found to correlate well with the experimental data with coefficient correlation (R²) of 0.941, 0.940 and 0.917 respectively. Therefore, Chrastil model, Del Valle-Aguilera model and Adachi-Lu model are suitable to represent the thermodynamic modeling of solubility date seed oil in SC-CO₂ at temperature range 40-80°C and pressure range 27.6-55.2MPa.